2016
DOI: 10.1126/scitranslmed.aaf3735
|View full text |Cite
|
Sign up to set email alerts
|

Homoharringtonine (omacetaxine mepesuccinate) as an adjunct for FLT3 - ITD acute myeloid leukemia

Abstract: An in vitro drug-screening platform on patient samples was developed and validated to design personalized treatment for relapsed/refractory acute myeloid leukemia (AML). Unbiased clustering and correlation showed that homoharringtonine (HHT), also known as omacetaxine mepesuccinate, exhibited preferential antileukemia effect against AML carrying internal tandem duplication of fms-like tyrosine kinase 3 (FLT3-ITD). It worked synergistically with FLT3 inhibitors to suppress leukemia growth in vitro and in xenogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 38 publications
3
62
0
Order By: Relevance
“…To determine if CB-839 will effectively combine with another drug that induces mitochondrial ROS, we next explored homoharringtonine (HHT). HHT is a protein translation inhibitor indicated for the treatment of tyrosine kinase inhibitor-resistant CML (20), which was recently found to effectively combine with FLT3 inhibitors for the treatment of AML (21). We have previously shown that drugs that combine well with FLT3 inhibitors are frequently potent inducers of mitoROS (10).…”
Section: Resultsmentioning
confidence: 99%
“…To determine if CB-839 will effectively combine with another drug that induces mitochondrial ROS, we next explored homoharringtonine (HHT). HHT is a protein translation inhibitor indicated for the treatment of tyrosine kinase inhibitor-resistant CML (20), which was recently found to effectively combine with FLT3 inhibitors for the treatment of AML (21). We have previously shown that drugs that combine well with FLT3 inhibitors are frequently potent inducers of mitoROS (10).…”
Section: Resultsmentioning
confidence: 99%
“…To determine if CB-839 will effectively combine with another drug that induces mitochondrial ROS, we next explored homoharringtonine (HHT). HHT is a protein translation inhibitor indicated for the treatment of tyrosine kinase inhibitor-resistant CML 23 that was recently found to effectively combine with FLT3 inhibitors for the treatment of AML 24 . We have previously shown that drugs that combine well with FLT3 inhibitors are frequently potent inducers of mitoROS 14 .…”
Section: Resultsmentioning
confidence: 99%
“…For example, homoharringtonine (also known as omocetaxine, synribo) is an inhibitor of the first round of peptide bond formation by the ribosome that has been approved for treatment of tyrosine kinase inhibitor-resistant CML (163) and is currently in clinical trials for AML (43,164,165). Several eukaryotic-specific inhibitors that bind the ribosomal E-site, e.g.…”
Section: Therapeutic Strategiesmentioning
confidence: 99%